2017
DOI: 10.1002/ajum.12052
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a virtual reality simulator for the use of transvaginal ultrasonography in gynaecology and early pregnancy

Abstract: Introduction: The objective was to validate a virtual reality simulation ultrasound model as a tool for training in the use of transvaginal ultrasonography in gynaecology and early pregnancy. Methods: Three separate groups consisting of novice and intermediate level residents as well as expert ultrasound examiners were recruited to the study. All were asked to answer a questionnaire regarding demographic data and ultrasound experience. They subsequently completed two modules: basic gynaecology and early pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Two thirds felt that it would improve clinical skills but given lack of practical exposure these perceptions were theoretical. Another study of twenty-four participants limited perception to questionnaire analysis [14]. Another study of 15 doctors, showed improved confidence, more systematic approach and documentation [16] but also limited perceptions to questionnaire analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two thirds felt that it would improve clinical skills but given lack of practical exposure these perceptions were theoretical. Another study of twenty-four participants limited perception to questionnaire analysis [14]. Another study of 15 doctors, showed improved confidence, more systematic approach and documentation [16] but also limited perceptions to questionnaire analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the publications to date that studied trainee's perspectives of TVUS simulation training, most are quantitative studies using questionnaires or self-assessed confidence scores [10,[13][14][15][16][17] with one mixed methods study [12]. In contrast, qualitative research allows use of open-ended questions that aim to explore what is important to the trainee themselves.…”
Section: Introductionmentioning
confidence: 99%
“…These technologies offer a lowrisk opportunity for trainees to acquire basic skills in a safe environment. 39 The ethical case for promoting simulation training is strong, allowing trainees to increase their exposure without compromising patient care. Telesimulation refers to the use of simulation training with the trainer and trainee locations connected via the internet.…”
Section: Telesimulation Training and Assessmentmentioning
confidence: 99%
“…Technology‐based simulation refers to the use of ultrasound model trainers, box trainers for laparoscopy and hysteroscopy, and virtual reality simulators. These technologies offer a low‐risk opportunity for trainees to acquire basic skills in a safe environment 39 . The ethical case for promoting simulation training is strong, allowing trainees to increase their exposure without compromising patient care.…”
Section: Technology Applications To Facilitate Remote Trainingmentioning
confidence: 99%
“…Some studies examined the question of validity concurrently or in isolation, so there is limited evidence on construct validity of simulators. 11,14,29,[48][49][50] Though literature on the use of US simulation is sparse, it consistently showed its usefulness in US education in OB GYN.…”
Section: Validity Of Various Simulatorsmentioning
confidence: 99%